Is group A thawed plasma suitable as the first option for emergency release transfusion? (CME). Issue 7 (8th January 2014) - Chhibber, Vishesh; Greene, Mindy; Vauthrin, Michelle; Bailey, Jeff; Weinstein, Robert
<x xml:space="preserve">Abstract</x> Background Group AB plasma, which lacks anti‐A and anti‐B isohemagglutinins, is issued for emergency transfusion when a patient's ABO group is unknown, but the relative scarcity of group AB blood donors limits its availability. We sought to establish a thawed plasma inventory to improve the rapid availability of plasma in the emergency release setting but were concerned about potential wastage of group AB plasma. Study Design and Methods Recognizing that plasma‐incompatible apheresis platelets are routinely transfused and only rarely result in hemolytic reactions if the donor is blood group O, and considering that group A plasma would be compatible with approximately 85% of our patient population, we instituted an emergency release policy whereby thawed group A plasma is issued to all patients of unknown blood group or if compatible plasma is not available. ABO‐compatible plasma is then issued, if needed, once the patient's blood group is determined. We prospectively assessed the outcomes of all patients who received incompatible plasma under our policy. Results During the first 5 years under this policy, 385 emergency release requests for plasma were received by our blood bank. Among them, 23 group B or AB patients met criteria for receiving a median of 2 units of incompatible group A plasma. No hemolytic transfusion reactions or other adverse events related to transfusion were seen in any of these 23 patients. Conclusion We propose that group A plasma may be an acceptable alternative to AB plasma as the first option in the emergency release setting.